2012
DOI: 10.1038/ejhg.2012.202
|View full text |Cite
|
Sign up to set email alerts
|

Refractory epilepsy and mitochondrial dysfunction due to GM3 synthase deficiency

Abstract: We report two children, born from consanguineous parents, who presented with early-onset refractory epilepsy associated with psychomotor delay, failure to thrive, blindness and deafness. Polarographic and spectrophotometric analyses in fibroblasts and liver revealed a respiratory chain (RC) dysfunction. Surprisingly, we identified a homozygous nonsense mutation in the GM3 synthase gene by using exome sequencing. GM3 synthase catalyzes the formation of GM3 ganglioside from lactosylceramide, which is the first s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
107
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 25 publications
3
107
0
1
Order By: Relevance
“…2), although we did not measure the activity of GM3 synthase in vitro. Increased lactate levels seen in the present study might suggest the secondary mitochondrial dysfunction due to GM3 synthase deficiency [Fragaki et al, 2013]. Yoshikawa et al reported that ganglioside GM3 is essential for the proper organization and maintenance of stereocilia in auditory hair cells, and therefore GM3 synthase deficiency can result in hearing loss [Inokuchi, 2011;Yoshikawa et al, 2015].…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…2), although we did not measure the activity of GM3 synthase in vitro. Increased lactate levels seen in the present study might suggest the secondary mitochondrial dysfunction due to GM3 synthase deficiency [Fragaki et al, 2013]. Yoshikawa et al reported that ganglioside GM3 is essential for the proper organization and maintenance of stereocilia in auditory hair cells, and therefore GM3 synthase deficiency can result in hearing loss [Inokuchi, 2011;Yoshikawa et al, 2015].…”
Section: Discussionmentioning
confidence: 49%
“…As shown in Figure 1C, there have been only two homozygous mutations reported to date: c.862C>T (p.Arg288 Ã ) and c.994G>A (p.Glu332Lys). The protein from the nonsense mutation, c.862C>T, was truncated between L-and S-motifs, which has been reported in Old Order Amish patients [Simpson et al, 2004;Fragaki et al, 2013;Wang et al, 2013]. The other mutation, c.994G>A in an African-American family, was within the S-motif, which might result in disturbed function of S-motif, interacting with the lactosylceramide acceptor and a sugar donor [Boccuto et al, 2014].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations